Mandelshtam and Dante: The Russian Connection - Titus, Julia (Spunti e Ricerche, 2022)
Through the prism of close reading this comparative essay focuses on Dante’s influence on one of the greatest poets of the Russian Silver Age, Osip Mandelshtam (1891–1938). The author first analyzes Mandelshtam’s theoretical essay “Conversation about Dante,” where Mandelshtam not only provided his critical commentary to The Divine Comedy but formulated his views on poetry as the art form. Several poems by Mandelshtam, written when he was in political exile in Voronezh, directly inspired by Dante’s imagery and poetics, are also discussed.